Product Development of Toddy Palm Seeds in Sugar Palm Juice Packed in Retort Pouch - Klamsakul, Supatra; Ratchatachaiyos, Kanya; NimKian, Bumpen; Chomphuthong, Prakard (Journal of Food Technology, Siam University, 2024)
Nowadays, palm sugar is increasingly processed into various products. This research aims to increase the product value of palm sugar seeds in sugar palm juice packed in retort pouches. Analysis results of toddy palm seed maturation 2 stages showed that young palm exhibited favorable characteristics with the highest liking score of 7.96 points, hardness value 208.83 newtons, soluble solids 7.03 oBrix, pH 7.43. The study of adding fruit pulp at 10, 20 and 30 % into fresh palm juice resulted in the highest liking score of 7.90 points at a 20 % fruit pulp. Furthermore, optimal heat penetration conditions, defined by F0 at temperature of 121 °C for 6.6, 8.5 and 10.9 minutes at F0 6.6 minutes presented superior sensory attributes, including color, smell, taste, and texture at of 7.88, 7.78, 6.98, 7.94 and 7.42 points, respectively. Microbiological analysis revealed the absence of total microorganisms, yeast and mold, heat-tolerant microorganisms, and microorganisms associated with sour taste. Sensory evaluation scores showed a decline in ratings as the storage time of palm sugar increased. Scores ranged from 8.62 to 7.12 points for characteristics rated as 'very like' to 'like moderately’ and none of microorganisms were detected during 4 month of storage.